2020
DOI: 10.34117/bjdv6n5-447
|View full text |Cite
|
Sign up to set email alerts
|

Functional exercise circuit reduce the metabolic risk factor in older people in three months of training

Abstract: Functional exercise circuit reduce the metabolic risk factor in older people in three months of training Circuito de exercício funcional reduz o fator de risco metabólico em idosos em três meses de treinamento

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
2
0
0
Order By: Relevance
“…This indicates that regardless the type of motor task performed by the older adult, if it is prescribed at adequate intensity, it can produce physiological effects. The physiological effects of dual-task training have been previously reported 17,31 and it was also observed in our study with the increase in the antioxidant capacity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This indicates that regardless the type of motor task performed by the older adult, if it is prescribed at adequate intensity, it can produce physiological effects. The physiological effects of dual-task training have been previously reported 17,31 and it was also observed in our study with the increase in the antioxidant capacity.…”
Section: Discussionsupporting
confidence: 89%
“…It is well established that aerobic and strength exercises from moderate to high intensity generate effects on body composition, increasing muscle mass and decreasing the fat percentage 29,30 , which generate important bene ts in the prevention and treatment of other metabolic comorbidities. Although the objective of the dual-task training is not to change body composition, a previous study with this protocol showed improvements in the lipid pro le 31 , which could be associated with the reduction in fat mass observed in the present study. This indicates that regardless the type of motor task performed by the older adult, if it is prescribed at adequate intensity, it can produce physiological effects.…”
Section: Discussionsupporting
confidence: 46%